2010
DOI: 10.1159/000316169
|View full text |Cite
|
Sign up to set email alerts
|

The Burden of Nail Psoriasis: An Introduction

Abstract: Nail involvement is an extremely common feature of psoriasis and affects approximately 50% of patients. Despite this, it is an often overlooked feature of the disease, and treatment tends to be focused on clearing the cutaneous component of psoriasis. Clinical manifestations of nail psoriasis are pitting, discolouration, onycholysis and subungual hyperkeratosis as well as nail plate crumbling and splinter haemorrhages. Nail psoriasis is associated with discomfort in many patients and leads to significant funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
101
0
12

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(114 citation statements)
references
References 33 publications
1
101
0
12
Order By: Relevance
“…52 Treating patients for more than 1 to 2 years without nephrology consultation is not recommended because of CsA-associated risk of nephrotoxicity. 17,52 Patients taking long-term therapy are also at risk of gingival hyperplasia, so yearly dental examinations are advised. 52 The current recommendations for managing nephrotoxicity are reducing the dose of CsA by 25% to 50% (equivalent to 0.5 to 1.0 mg/kg/day) if serum creatinine levels increase more than 25% to 30% above baseline on 2 occasions (repeated measurements separated by 2 weeks).…”
Section: Monitoringmentioning
confidence: 99%
“…52 Treating patients for more than 1 to 2 years without nephrology consultation is not recommended because of CsA-associated risk of nephrotoxicity. 17,52 Patients taking long-term therapy are also at risk of gingival hyperplasia, so yearly dental examinations are advised. 52 The current recommendations for managing nephrotoxicity are reducing the dose of CsA by 25% to 50% (equivalent to 0.5 to 1.0 mg/kg/day) if serum creatinine levels increase more than 25% to 30% above baseline on 2 occasions (repeated measurements separated by 2 weeks).…”
Section: Monitoringmentioning
confidence: 99%
“…Van Laborde et al have shown that there is an 80% to 90% lifetime incidence of nail involvement in psoriatic patients [4]. The presence of nail involvement of psoriasis is associated with an increase in patient-reported pain complaints, functional impairment and social burden, resulting in a significant restriction of daily activities and quality of life as well as resistance to treatment [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…%1-10 hastada ise psoriazis sadece tırnak tutulumu ile seyredebilir (3). Psoriazis hastalarının %80-90'ında hayatlarının bir bölümünde tırnak tutulumu görülmektedir (4).Psoriazis tırnak tutulumu tanısı klinik ve histopatolojik olarak konmaktadır.…”
Section: Introductionunclassified